The United Kingdom’s response to the 2014-2018 Islamic State Terrorist Group attacks - Dewi Nawar Sri Juita (Faculty of Social and Political Science, Universitas Airlangga, 2021)
Advancements in technology, information, and communication have transformed warfare from a conventional method to psychological warfare (psywar). In the past, warfare was heavily associated with various weapons, such as rifles, bombs, or even nuclear power, to attack an area for specific purposes. In the modern era, warfare is more concerned about technology and information superiority to threaten the enemy faster and more robust. Modern warfare targets the psychology of society in order to win the war. Islamic State (IS) has attracted the world’s attention for its successful strategy in using Twitter in waging war on a country, in this case, the United Kingdom. The purpose of this research is to describe the United Kingdom government’s response in fighting Islamic State attacks on Twitter. This research uses descriptive methods by collecting data from books, the internet, journals, and scientific articles. This study indicates that the United Kingdom responds to Islamic State attacks through two patterns, hard and soft power. The hard power method is carried out through intelligence, police, and economic power to collaborate with international organizations such as the United Nations. The soft power pattern was implemented by creating official state Twitter accounts such as @UKAgainstDaesh, @coalition, @TerrorismPolice, and collaboration with the Global Internet Forum Counter-Terrorism (GIFCT). This strategy plays an essential role in stopping the spread of online terrorism-related content online by blocking related photos, videos, and texts of terrorism.